2021
DOI: 10.1371/journal.pone.0249074
|View full text |Cite
|
Sign up to set email alerts
|

A review of reported network degree and recruitment characteristics in respondent driven sampling implications for applied researchers and methodologists

Abstract: Objective Respondent driven sampling (RDS) is an important tool for measuring disease prevalence in populations with no sampling frame. We aim to describe key properties of these samples to guide those using this method and to inform methodological research. Methods In 2019, authors who published respondent driven sampling studies were contacted with a request to share reported degree and network information. Of 59 author groups identified, 15 (25%) agreed to share data, representing 53 distinct study sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Table 1 details the achieved population-level homophily and relative activity for each of the simulated populations. A survey of RDS studies indicated that degree distributions in many real-world populations are approximately log-normally distributed ( Avery et al 2021 ). To allow comparison with previous literature and estimate real-world performance, Figure 2 shows the effect of personal network degree distribution on estimator variability for populations with equal relative activity and no homophily.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 details the achieved population-level homophily and relative activity for each of the simulated populations. A survey of RDS studies indicated that degree distributions in many real-world populations are approximately log-normally distributed ( Avery et al 2021 ). To allow comparison with previous literature and estimate real-world performance, Figure 2 shows the effect of personal network degree distribution on estimator variability for populations with equal relative activity and no homophily.…”
Section: Resultsmentioning
confidence: 99%
“…Previous RDS validation research has relied on degree distributions generated using ERGM or Poisson distributions, which have less variation than degrees reported by participants in real-world studies. A comprehensive survey of RDS samples showed that self-reported degree is log-normally distributed across a variety of population types (sex workers, men who have sex with men, people who inject drugs, migrants) and geographies (North America, India, Europe) ( Avery et al 2021 ). The degree distributions of the Project 90 and Large Facebook Pages networks ( Figure S5 in the online supplement ) indicate similar distributions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, our interpretations in Table 1 hold under the assumptions of sufficient confounder control for the mediator–outcome relationship (VanderWeele and Robinson, 2014) and no exposure-induced mediator–outcome confounding. Primary findings are presented without including RDS weights, as no consensus exists on their incorporation in natural effect models (Avery et al , 2021; Gile et al , 2018), although there exists ongoing discussion (Yauck et al , 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Under several assumptions, including that the sample has sufficiently many waves, that the population comprises a connected underlying social network, and that recruitment is random, the RDS sampling process approximates a successive sampling process over the network (Gile, 2011) and reported degree informs an individual's inclusion probability. Numerous surveys have been conducted worldwide using RDS to sample hidden populations, especially for the purposes of estimating trends in HIV prevalence and risk factors (Johnston et al, 2013(Johnston et al, , 2016(Johnston et al, , 2019Malekinejad et al, 2008;Avery & Rotondi, 2020;Avery et al, 2021). Inferential methods for RDS data, as well as their limitations, have been well-studied (Gile et al, 2018).…”
Section: Respondent-driven Samplingmentioning
confidence: 99%